Analysis of Infrared Radiation at an Air-Water Interface - Handler, Robert A.; Judd, K. Peter (Frontiers in Mechanical Engineering, 2018)
The problem of determining the strength of the infrared radiation from an air-water interface has been addressed analytically. The approach taken here is to express the Planck spectrum as a linear function of the temperature, an approximation valid for small variations of the temperature from the surface temperature, and to assume a linear temperature profile across the thermal boundary layer. The main result shows that the deviation of the surface radiation intensity from the Planck spectrum due solely to thermal stratification, is linearly proportional to the temperature change across the thermal boundary layer and the optical depth, but is inversely proportional to the thermal boundary layer thickness. This signal was shown to be about one order of magnitude greater than the noise level expected from modern CCD IR sensors at a wavelength of about 3.8 microns. It is suggested that controlled laboratory experiments be conducted to verify these theoretical estimates.